2017
DOI: 10.5604/01.3001.0010.5040
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge of students in Opole Medical School on honorary blood donation and transfusion medicine – analysis of own research/ Wiedza studentów Państwowej Medycznej Wyższej Szkoły Zawodowej w Opolu dotycząca honorowego krwiodawstwa i leczenia krwią – analiza badań własn ych

Abstract: Background: The ultimate purpose of blood donation is to obtain blood from healthy donors for use by those who require a blood transfusion. This becomes possible due to a solid base of blood donors. Oftentimes, students are recruited as they represent a large potential pool of donors. The results of this survey indicate the areas that require focus in order to promote voluntary blood donation. Aim of the study: To determine the amount of knowledge that Opole Medical School students have concerning blood donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our study results are confirmed by those of Czapla et al (2015), where 82% of students believed that the risk of becoming addicted to blood donation is a myth [11]. In another study, Czapla et al (2017) analyzed the perception of myths on blood donation among students to find that most of them think blood donation is non-addictive (82%) [12]. Studies by Pirincci et al demonstrated that only 1% of responders believed that regular blood donation may lead to addiction [13].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study results are confirmed by those of Czapla et al (2015), where 82% of students believed that the risk of becoming addicted to blood donation is a myth [11]. In another study, Czapla et al (2017) analyzed the perception of myths on blood donation among students to find that most of them think blood donation is non-addictive (82%) [12]. Studies by Pirincci et al demonstrated that only 1% of responders believed that regular blood donation may lead to addiction [13].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, 98.0% of responders who donated the largest volume of blood, denied the occurrence of such phenomenon. Czapla demonstrated that the highest percentage of her student responders (65%) believed that excessive RBC production c is in no way associated with regular, voluntary blood donation [12]. In her analysis, Orzeł-Nowak demonstrated that only 5.2% of responders felt anxiety over excessive production of RBCs after regular donations [15].…”
Section: Discussionmentioning
confidence: 99%